L’invention de la médiation paysagère - Rémi Bercovitz (Projets de Paysage)
Since the 1980s, the notion of mediation has flourished and there has been exponential growth in mediation practices and the use of mediators. Landscape architecture has also been affected by this booming trend which resulted in the emergence of the idea of landscape mediation at the end of this decade. The first theoretical constructs and practical applications in this field came from applied research and scientific experimentation mainly conducted by agronomists and geographers. The purpose of this article is to carry out a critical analysis of the body of research produced by these researchers during the 1990s and 2000s. On this basis, we will seek to shed light on the context and theoretical, epistemological and methodological assumptions underlying this pioneering research which very often addresses local development issues in rural areas. The aim is to describe and analyse the concepts developed as well as the tools and methods employed.